EDUKASI INTEGRASI PRAKTIK PENGELOLAAN KEUANGAN HIJAU DAN PEMASARAN BERKELANJUTAN PADA USAHA TANI BB INTEGRATED FARMING (BIF) - Oktaviani, Siska Aprilia; Pinandita, Candra Pramula; Sugiartono, Endro; Hartanto, Sugeng; Harkat, Avisenna (Jurnal Pengabdian Masyarakat dan Lingkungan, 2024)
This community service activity aims to enhance farmers' understanding and skills in adopting green finance and sustainable marketing strategies to support sustainable agricultural practices at BB Integrated Farming, Silo District, Jember Regency. The program involves a series of training sessions, mentoring, and interactive discussions designed to equip farmers with the knowledge and tools necessary for managing green finance, developing sustainable marketing strategies, and understanding market dynamics. The results of this activity show a significant increase in farmers' understanding and skills, evidenced by better post-test results compared to pre-test scores. Farmers are now able to adopt environmentally friendly practices, access sustainable financing, and implement effective marketing strategies. This program not only contributes to improving the environmental and economic performance of farmers but also supports local and global food security by promoting more productive and sustainable agricultural practices.